Responsive Neurostimulation of the Mesial Temporal White Matter in Bilateral Temporal Lobe Epilepsy. Issue 2 (7th October 2020) - Nunna, Ravi S; Borghei, Alireza; Brahimaj, Bledi C; Lynn, Fiona; Garibay-Pulido, Diego; Byrne, Richard W; Rossi, Marvin A; Sani, Sepehr
Abstract: BACKGROUND: Responsive neuromodulation (RNS) is a treatment option for patients with medically refractory bilateral mesial temporal lobe epilepsy (MTLE). A paucity of data exists on the feasibility and clinical outcome of hippocampal-sparing bilateral RNS depth lead placements within the parahippocampal white matter or temporal stem. OBJECTIVE: To evaluate seizure reduction outcomes with at least a 1-yr follow-up in individuals with bilateral MTLE undergoing hippocampus-sparing implantation of RNS depth leads. METHODS: A retrospective analysis of prospectively collected data was performed on patients at our institution with bilateral MTLE who were implanted with RNS depth leads along the longitudinal extent of bitemporal parahippocampal white matter or temporal stem. Baseline and postoperative seizure frequency, previous surgical interventions, and postimplantation electrocorticography and stimulation data were analyzed. RESULTS: Ten patients were included in the study (7 male, 3 female). Overall seizure frequency declined by a median 44.25% at 3.13 yr (standard deviation 3.31) postimplantation. Four patients (40%) achieved 50% responder rate at latest follow-up. Two of four patients with focal onset bilateral tonic-clonic seizures became completely seizure-free. Forty percent of patients were previously implanted with a vagus nerve stimulator, and 20% underwent a prior temporal lobectomy. All depth lead placements were confirmed as radiographically located in the parahippocampal white matter or temporal stem without hippocampus violation. There were no cases of lead malposition. CONCLUSION: Extrahippocampal or temporal stem white matter targeting during RNS surgery for bitemporal MTLE is feasible and allows for electrographic seizure detection. Larger controlled studies with longer follow-up are needed to validate these preliminary findings.